Estimation of phagocytic activity of polymorphonuclear leukocytes in chronic and aggressive periodontitis patients with nitroblue tetrazolium test - Gooty, Jagadish Reddy (J Indian Soc Periodontol, 2019)
CONTEXT: The phagocytic activity of polymorphonuclear leukocytes (PMN) is influenced by the type of disease entity, i.e., chronic generalized periodontitis, generalized aggressive periodontitis, and chronic generalized gingivitis. AIMS: The purpose of this experimental study was to evaluate the phagocytic activity of PMN in patients with chronic generalized periodontitis, generalized aggressive periodontitis, and chronic generalized gingivitis. MATERIALS AND METHODS: A total of 60 patients, 20 patients with chronic generalized periodontitis, 20 patients with generalized aggressive periodontitis, and 20 patients with chronic generalized gingivitis were selected for this study. Blood samples were collected from the patients. Peripheral smears were prepared from the samples, and the slides were stained using nitroblue tetrazolium test, and the phagocytic activity of the neutrophils was compared using the test results. STATISTICAL ANALYSIS USED: Intragroup comparison using Mann–Whitney U-test and intergroup comparison using Kruskal–Wallis one-way ANOVA test were done. RESULTS: The results of the present study suggest that PMN phagocytic defect was present in most of the patients affected by generalized aggressive periodontitis; however, the phagocytic defect cannot be attributed to age, sex, or clinical parameters such as the plaque index or gingival index and probing pocket depths. CONCLUSIONS: The phagocytic activity of neutrophils in generalized aggressive periodontitis was low compared to chronic generalized periodontitis and chronic generalized gingivitis.